PL04: A randomized controlled trial comparing prescribed light exercise to standard management for emergency department patients with acute mild traumatic brain injury. (May 2020) - Varner, C.; Thompson, C.; de Wit, K.; Borgundvaag, B.; Houston, R.; McLeod, S.
Abstract : Introduction: The emergency department (ED) is often the first point of health care contact for patients with mild traumatic brain injury (MTBI). Spontaneous resolution occurs in most patients within 7 days, yet 15-30% will develop post-concussion syndrome (PCS). Given the paucity of effective management strategies to prevent PCS and emerging evidence supporting exercise, the objective of this study was to evaluate the impact of prescribed early light exercise compared to standard discharge instructions for acute MTBI patients in the ED. Methods: This was a randomized controlled trial conducted in three Canadian EDs. Consecutive, adult (18-64 years) ED patients with a MTBI sustained within the preceding 48 hours were eligible for enrollment. The intervention group received discharge instructions prescribing 30 minutes of daily light exercise (e.g., walking), and the control group was given standard MTBI instructions advising gradual return to exercise following symptom resolution. Participants documented their daily physical activities and completed follow-up questionnaires at 7, 14, and 30 days. The primary outcome was the proportion of patients with PCS at 30 days, defined as the presence of ≥ 3 symptoms on the Rivermead Post-concussion Symptoms Questionnaire (RPQ) at 30 days. Results: 367 patients were enrolled (control n = 184; intervention n = 183). Median age was 32 years and 201 (57.6%) were female. There was no difference in the proportion of patients with PCS at 30 days (control 13.4 vs intervention 14.6; Δ1.2, 95% CI: -6.2 to 8.5). There were no differences in median change of RPQ scores (control 14 vs intervention 13; Δ1, 95% CI: -1 to 4), median number of return health care provider visits (control 1 vs intervention 1; Δ0, 95% CI: 0 to 0), or median number of missed school or work days (control 2 vs intervention 2; Δ0, 95% CI: 0 to 1) at 30 days. There was a nonsignificant difference in unplanned return ED visits within 30 days (control 9.9% vs intervention 5.6%; Δ1, 95% CI: -1.4 to 10.3). Participants in the control group reported fewer minutes of light exercise at 7 days (30 vs 35; Δ5, 95% CI: 2 to 15). Conclusion: To our knowledge, this is the first randomized trial of prescribed early light exercise for adults with acute MTBI. There were no differences in recovery or healthcare utilization outcomes. Results suggest prescribed early light exercise should be encouraged as tolerated at ED discharge following MTBI, but exercise prescription alone is not sufficient to prevent PCS.